IMPLEMENTASI ALGORITMA APRIORI UNTUK MENENTUKAN KEPUASAN MAHASISWA TERHADAP PELAYANAN SIM ONLINE UNIVERSITAS WIDYAGAMA MALANG - Ibnu Mubarok; Fitri Marisa; Dwi Purnomo (Universitas Merdeka Malang, 2017)
Information system is a medium to accommodate an activity that takes place in an agency or institution, whether it is administrative activities and activities in a non-administration. Therefore, the information system is needed as supporting the publishing or storage database of an agency. A good information system will greatly support the educational activities of an institution or educational institution one of them is academic system information system which includes data processing related data entities, lessons, schedules, and so forth. From the definition of standard website quality, it can be concluded that the quality of website services in university widyagama malang not reach the criteria specified by the standard ISO 8402. So that most of the users among university students Widyagama Malang many who complain to the service website itself, Are: a lot of unpublished student value, delinquent financing arrears, and many other service deficiencies on the website. So that made the system Implementation of Apriori Algorithm To Determine Student Satisfaction Of Online SIM Service Widyagama University of Malang. To find the level of student satisfaction dihadapat wice online service wydiagama unfortunate. DOI: https://doi.org/10.26905/jtmi.v3i1.1244